Estimation of surface water content at the Tianwen-1 Zhurong landing site - Xiang Zhou; Yang Liu; Xing Wu; ZhenXing Zhao; YongLiao Zou (Earth and Planetary Physics, 2023)
China’s first Mars rover, Zhurong, successfully landed in the south of Utopia Planitia. The surface water content at the landing area can provide constraints on mineral formation conditions and help us better understand the evolution of the Martian aqueous and geological environment. In this work, the surface kinetic temperature of the Zhurong landing area was derived by analyzing data from the Mars Express Observatoire pour la Minéralogie, l’Eau, les Glaces et l’Activité (OMEGA) spectrometer. Using the Discrete Ordinate Radiative Transfer (DISORT) model, we performed atmospheric correction and thermal correction for the OMEGA data to obtain the surface effective single-particle absorption thickness (ESPAT) parameter to evaluate the surface water content. The surface water content distribution at the landing area was relatively uniform at a lateral scale of ~10 km. At the Zhurong landing site, the surface water content in the topmost layer (a few hundred micrometers) of the regolith was 5−8 weight percent water (wt% H2O), assuming surface particle sizes of <45 μm, or 1.6−2.5 wt% H2O, assuming surface particle sizes in the range of 125−250 μm. The Mars Surface Composition Detector (MarSCoDe) onboard Zhurong also observed significant H2O/OH signals in the landing area. Our results provide an important regional context for the hydration state of the area and can be further verified by the H content derived from the Laser-Induced Breakdown Spectrometer (LIBS) data of MarSCoDe.